Post-Partum Thrombotic Thrombocytopenic Purpura (TTP) in a Patient with known Idiopathic (Immune) Thrombocytopenic Purpura: a case report and review of the literature - Al-Husban, Naser (J Med Case Rep, 2018)
BACKGROUND: Incidences of immune thrombocytopenic purpura occur in 1 in every 1000–10,000 pregnancies accounting for 3% of all thrombocytopenic pregnancies. A pre-existing immune thrombocytopenic purpura is known to be a risk factor for developing thrombocytopenia during pregnancy. We present here the treatment regime and management of a patient with known immune thrombocytopenic purpura who developed postpartum thrombotic thrombocytopenia with atypical response to traditional therapy. Pregnant women are more vulnerable to immune thrombocytopenic purpura or thrombotic thrombocytopenia. Pregnancy or postpartum thrombotic thrombocytopenia accounts for 10–25% of all thrombotic thrombocytopenia. CASE PRESENTATION: This case report deals with the treatment regime and management of a patient with known immune thrombocytopenic purpura who developed postpartum thrombotic thrombocytopenia. A 30-year-old Middle Eastern woman, with a prior diagnosis of chronic immune thrombocytopenic purpura had remained off-the-treatment for many years. After primary unexplained infertility for 8 years, for which she underwent six failed trials of in vitro fertilization, she delivered a healthy baby through caesarean section. Two days post-surgery, she had persistent thrombocytopenia, ecchymoses, bruises, and hemolysis. Her blood film revealed leukoerythroblastic anemia. Her blood tests also revealed a very low level of haptoglobin, and low level of ADAMTS13. A diagnosis of thrombotic thrombocytopenia was suspected. Plasma exchange therapy was started with partial response. We showed that rituximab in conjunction with mycophenolate mofetil following plasma exchange therapy was effective in controlling the low platelet count in our patient. CONCLUSIONS: Rituximab in conjunction with mycophenolate mofetil following plasma exchange therapy was effective in controlling the low platelet count in our patient. Only two doses of rituximab were sufficient to normalize our patient. We present here a case of safe and effective use of rituximab in pregnancy-induced thrombotic thrombocytopenia.